2020
DOI: 10.3390/ijms21020415
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study on the Effect of Biophysical Therapy on Salivary Alpha-Amylase as a Surrogate Measure of Anxiety/Stress: In Search of a Novel Noninvasive Molecular Approach for the Management of Stress

Abstract: Anxiety and depression impact dramatically on public health, underlying the importance of alternative cost-effective treatments. Previous studies have shown that biophysical treatment can significantly reduce anxiety symptoms and recently, salivary alpha-amylase (SAA) has been identified as an objective correlate of the sympathetic-parasympathetic imbalance related to increased stress burden, defined as allostatic load. The aim of this study was to evaluate the effect of biophysical therapy on SAA levels, in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…In general, via our measurement system, we detected the transfer of the UHD signal of a-IFNγ solutions in all tested situations. The detection thus corroborates similar reported findings from other groups [ 2 , 35 , 37 , 38 , 39 , 40 , 41 , 51 , 52 , 53 , 54 ]. Even the solvent (water) UHD signal—presumably stemming only from striking—was detected, although the detection was much weaker than the one produced by the other two signals.…”
Section: Discussionsupporting
confidence: 92%
“…In general, via our measurement system, we detected the transfer of the UHD signal of a-IFNγ solutions in all tested situations. The detection thus corroborates similar reported findings from other groups [ 2 , 35 , 37 , 38 , 39 , 40 , 41 , 51 , 52 , 53 , 54 ]. Even the solvent (water) UHD signal—presumably stemming only from striking—was detected, although the detection was much weaker than the one produced by the other two signals.…”
Section: Discussionsupporting
confidence: 92%
“…Measurement of salivary amylase is an indirect measurement of anxiety which is less reliable and facilities for this test are not available in our setup. [13][14] Spinal anesthesia in cesarean deliveries results in some degree of hypotension in almost all cases as represented in many international studies. [15][16] In this study we demonstrated that increased pre-operative anxiety was associated with a greater reduction in MAP after spinal anesthesia for cesarean delivery.…”
Section: Discussionmentioning
confidence: 99%
“…One such possibility involves the use of water in its mesoscopic, i.e., dynamically ordered, state. According to many researchers and their findings, its oscillation patterns can be changed as a consequence of the subtle field influence that induces or transfers order from a system to water [6][7][8]. Even if this supramolecular order of water is not universally recognized, it comprises many valuable empirical pieces of research and theoretical considerations comprising socalled water clusters [9][10][11], coherent domains [12], exclusion zone water [13] and other similar formations.…”
Section: Introductionmentioning
confidence: 99%